A comparison forecast volume of outbound containers in case of The Bangkok port Between Exponential Smoothing and ARIMA Model - et. al., Weerawit Lertthaitrakul, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This research aims to compare the forecast of container consumption between Exponential Smoothing and ARIMA methods and make a forecast volume of outbound containers from Bangkok Port. Using time series data of the quantity of containers departing from Bangkok ports from January 2011 to December 2020 from Port authority of Thailand. By using the criterion of the root mean squared error (RMSE), it was found that the ARIMA forecasting method was more suitable for this set of time series data than the Exponential Smoothing method. The ARIMA forecasting method was root mean square error (RMSE) is 3310.72 and the exponential smoothing method was root mean square error (RMSE) is 3381.09 However, both methods could be used combined for forecasting to serve as an appropriate forecast model.